Night of the Ninjas - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1995)
The magic tree house takes Jack and Annie back in time to feudal Japan where the siblings learn about the ways of the Ninja.
"A First stepping stone book."
"RL: 1.9 006-009"--Cover P. [4].
Keywords: Time travel -- Fiction; Magic -- Fiction; Ninja -- Fiction; Japan -- History -- Fiction